STRENGTHENING LOCAL WASTE GOVERNANCE IN INDONESIA: PARTICIPATORY APPROACHES, INSTITUTIONAL DYNAMICS, AND ETHICAL INTEGRATION - Arif, Fatimah; Alamsyah, Anggriani; Ahmad, Nurfadilah (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2026)
Plastic waste, with its wide-ranging implications, has become a critical concern in both environmental governance and public health, particularly in Indonesia. The problem is exacerbated by inadequate infrastructure, fragmented legal and institutional arrangements, and limited public awareness. This study explores how participatory governance, institutional reform, and the integration of ethical principles can enhance plastic waste management at the local level. Employing a qualitative approach, the study draws insights from in-depth interviews, document analysis, and field observations of community-based initiatives in urban areas. The findings indicate that strategies such as waste banks, Islamic-based environmental education, and public private partnerships have contributed to increased community participation and measurable waste reduction. Supporting factors include a clear legal framework, decentralized policy implementation, and collaboration with non-governmental actors. Nevertheless, persistent challenges such as infrastructural deficiencies, cultural resistance, and institutional constraints continue to hinder progress. By aligning formal policy instruments with local ethical norms and everyday practices, this study offers a context-sensitive approach to sustainable waste governance, which is particularly relevant for developing regions.